Tinjauan Yuridis terhadap Transaksi Jual Beli Tanah Melalui Internet Banking - Made Restu Hawiwie; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Jurnal Preferensi Hukum, 2021)
The development of information. technology today makes internet banking an alternative in land buying and selling transactions. With the emergence of this technology it makes it easy for land buying and selling transactions and increases cost and time efficiency. The researcher figures out the problem in this research first, how to arrange land buying and selling transactions through internet banking and second, how proof of payment via internet banking becomes a guideline for the preparation of land buying and selling. The research method used is a normative legal research method with a statutory study approach. The source of primary legal materials is the applicable laws and regulations and secondary legal materials namely literature. From the research results, it can be concluded that the arrangement of land safe and purchase transact ions through internet banking is regulated in Article 1320 and Article /457 KUHP, Article 19 VU /TE, and Article 19 paragraphs (1) and (2) UUPA, as well as PP Number 24 of 1997. Proof of payment via internet banking as the basis for drawing up a land safe and purchase deed is regulated in Article 5 paragraph (1) UV/TE.